Competency of Senior High School Teachers in Assessment and Reporting in Goa District, Philippines - Manigbas, Jimmy III; Luna, Yumi Vivien V. De (IJBLE Scientific Publications Community Inc., 2024)
This study investigated the competency of teachers in assessment and reporting. This involved the forty-five Senior High School teachers in the public secondary schools in the Department of Education (DepEd), Division of Camarines Sur, Goa District, Philippines. A survey questionnaire was utilized to gather data from the respondents on which strands and indicators were rooted in the Philippine Professional Standards for Teachers (PPST). The study results showed that teachers possessed a Moderately High Level of Competency in all strands along with assessment and reporting. The results further revealed a significant difference between teachers’ competency and demographic profiles when they are grouped according to their educational attainment and status of employment. It recommends that teachers should engage in professional development to continuously increase their knowledge and improve their teaching competencies to do better in their teaching profession.